Implementation of the CRISPR-Cas13a system in fission yeast and its repurposing for precise RNA editing. Issue 15 (31st May 2018) - Jing, Xinyun; Xie, Bingran; Chen, Longxian; Zhang, Niubing; Jiang, Yiyi; Qin, Hang; Wang, Hongbing; Hao, Pei; Yang, Sheng; Li, Xuan
Abstract: In contrast to genome editing, which introduces genetic changes at the DNA level, disrupting or editing gene transcripts provides a distinct approach to perturbing a genetic system, offering benefits complementary to classic genetic approaches. To develop a new toolset for manipulating RNA, we first implemented a member of the type VI CRISPR systems, Cas13a from Leptotrichia shahii (LshCas13a), in Schizosaccharomyces pombe, an important model organism employed by biologists to study key cellular mechanisms conserved from yeast to humans. This approach was shown to knock down targeted endogenous gene transcripts with different efficiencies. Second, we engineered an RNA editing system by tethering an inactive form of LshCas13a (dCas13) to the catalytic domain of human adenosine deaminase acting on RNA type 2 (hADAR2d), which was shown to be programmable with crRNA to target messenger RNAs and precisely edit specific nucleotide residues. We optimized system parameters using a dual-fluorescence reporter and demonstrated the utility of the system in editing randomly selected endogenous gene transcripts. We further used it to restore the transposition of retrotransposon Tf1 mutants in fission yeast, providing a potential novel toolset for retrovirus manipulation and interference.